Socioeconomic Inequities in Health Care Utilization in China. (May 2015) - Zhang, Xin; Wu, Qunhong; Shao, Yongxiang; Fu, Wenqi; Liu, Guoxiang; Coyte, Peter C.
The study assessed the present degree of inequity in health care utilization as well as the contributions of the main determinants in the context of expending health insurance coverage in China. Data were obtained from the 2008 National Health Services Survey (NHSS) in China. A concentration index was used to quantify the degree of income-related inequity in health care utilization. The need-standardized concentration indexes of outpatient care and inpatient care were 0.015 and 0.197, respectively. Income made the largest contribution to inequity favoring the better-off in the use of health care. The impacts of health insurance schemes on overall inequity varied according to the insurance memberships as well as types of services. The study revealed a pro-rich distribution of the probability of health care across income groups in China. Increased financial protection ability of medical insurance system remains a vital cornerstone to tackle the health care utilization inequity.